Causes and Consequences of Failed Mergers and Acquisitions : A Comparative Study - Sriram, Ronika (2025)
Although finance has been extensively examined, the ramifications of unsuccessful mergers and acquisitions (M&As) are still insufficiently investigated. This study examines two specific categories of merger failures: (i) transaction cancellations and (ii) post-merger demergers, together with their consequences for corporations, investors, and markets. The study employs an event study methodology and the Capital Asset Pricing Model (CAPM) to analyze aberrant returns surrounding significant dates. The analysis encompasses listed and delisted enterprises with accessible historical price data; companies that became private, discontinued operations, or were never separately traded were removed owing to a lack of data. Research indicates persistent negative anomalous returns associated with unsuccessful M&A events, underscoring their strategic and financial repercussions. This study contributes to the literature by comprehensively examining market reactions to M&A failures.